2018
DOI: 10.11648/j.cajph.20180405.14
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Anemia and Associated Factors Among Pregnant Women Visiting Public Health Institutions for Antenatal Care Services in Adama Town, Ethiopia

Abstract: Anemia is a global public health problem. It affects more than 2 billion people worldwide, both in developing and developed countries. It affects people of all age groups. However, it is more prominent in pregnant women. It is estimated that approximately 41.8% of pregnant women worldwide affected by anemia. Institution based cross sectional study design was employed. A total of 424 pregnant women visiting public Health Institutions in Adama Town for Antenatal Care service was randomly selected. Data was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
3
1
1
Order By: Relevance
“…Pregnant women of Mid Upper Arm Circumference (MUAC) less than 21cm were more likely to be anemic as compared to women not malnourished. The result of this study is comparable with the study conducted in Adama town, Jigjiga town, Gode town and Ilu Abba Bora zone [3236]. The similarity could be due the facts that under nutrition occur as a result of micro and macro nutrient deficiency and also anemia may occur as complication of malnutrition.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Pregnant women of Mid Upper Arm Circumference (MUAC) less than 21cm were more likely to be anemic as compared to women not malnourished. The result of this study is comparable with the study conducted in Adama town, Jigjiga town, Gode town and Ilu Abba Bora zone [3236]. The similarity could be due the facts that under nutrition occur as a result of micro and macro nutrient deficiency and also anemia may occur as complication of malnutrition.…”
Section: Discussionsupporting
confidence: 85%
“…The magnitude of anemia in this study is lower as compared with the studies done in Malaysia (33%) [28], Gana (51%) [29], and in Ethiopia: Tigray(36.1%) [30], Nekemte town (52%) [31], Adama (28.1%) [32], Gode town (56.8%)[33], Bisidimo (27.9) [34], Jijiga town (63.8%)[35] and Ilu Abba bora zone (31.5%) [36]. This difference might be due to the study period and the attention given for focused antenatal care and supplementation of iron sulfate throughout the pregnancy.…”
Section: Discussioncontrasting
confidence: 69%
“…Also, the women in the middle age group had some protection against anaemia at 28 weeks when haemodilution is not taken into consideration. This also falls in line with some studies that found isolated risk for specific age groups [71,72]. Also, the lack of association between anaemia at registration and age groups as observed in this study has also been reported in other studies [34,35,73].…”
Section: Plos Onesupporting
confidence: 93%
“…Also, the women in the middle age group had some protection against anaemia at 28 weeks when haemodilution is not taken into consideration. This also falls in line with some studies that found isolated risk for speci c age groups [70,71]. Also, the lack of association between anaemia at registration and age groups as observed in this study has also been reported in other studies [35,36,72].…”
Section: Socio-economic Characteristics Of the Respondentssupporting
confidence: 93%